Modeling of multiband/wideband stack series array antenna configuration for 5G application - Osman, Abdinasir Suleiman; Islam, Md. Rafiqul; Habaebi, Mohamed Hadi (IEEE, 2016)
In this paper, a novel V-band antenna configuration is modeled for multiband/wideband application. Multiband and wideband stack series array antenna were designed for the future 60 GHz in 5G application. Dual-layer substrate Technology was utilized in order to achieve a higher bandwidth which is needed to cover the V-band electromagnetic spectrum ranges from 50 -70 GHz. Total of 25 antenna array configurations were simulated and analyzed to develop the model. Proposed antenna can resonate at single band of (60GHz), dual band (57 GHz and 67.5) and triple band (54.82, 60.8 and 67.647GHz).The bandwidth of 14.836 GHz (53.33-68.186 GHz) and the gain of 13.05 dB were achieved by proposed antenna configurations. Simulated return loss, gain over the number of elements in upper/lower patches have been analyzed and presented. Many researchers are working on Vband antenna for wireless applications, However there are still some open issues such as the bandwidth and gain. The proposed array antenna provides flat gain, wide band width and higher efficiencies. All the proposed antenna configurations have shown a good candidate for 5G millimeter wave (mmwave) application. .